2002
DOI: 10.2165/00003088-200241110-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Intranasal Sumatriptan

Abstract: A substantial proportion of migraine patients have gastric stasis and suffer severe nausea and/or vomiting during their migraine attack. This may lead to erratic absorption from the gastrointestinal tract and make oral treatment unsatisfactory. For such patients, an intranasal formulation may be advantageous. Sumatriptan is a potent serotonin 5HT(1B/1D) agonist widely used in the treatment of migraine; the effectiveness of the intranasal formulation (20mg) has been well established in several clinical studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…(1) adequately describes the degradation kinetics of compound 4a. The kinetically determined pK a value is 9.26, which is close to, but lower than that for ionisation of the dimethylamino group in sumatriptan (pK a 9.63 [25]), and thus is also consistent with incorporation of the acyloxymethyl moiety at the indole nitrogen atom.…”
Section: Hydrolysis In Aqueous Bufferssupporting
confidence: 47%
“…(1) adequately describes the degradation kinetics of compound 4a. The kinetically determined pK a value is 9.26, which is close to, but lower than that for ionisation of the dimethylamino group in sumatriptan (pK a 9.63 [25]), and thus is also consistent with incorporation of the acyloxymethyl moiety at the indole nitrogen atom.…”
Section: Hydrolysis In Aqueous Bufferssupporting
confidence: 47%
“…Reports in the literature revealed that following intranasal administration, preferential nose-to-brain transport bypassing the BBB occurred due to the unique connection between the nose and the CNS. 11,12,32 The SME (intranasal) shows significantly higher brain/ blood ratio at 0.5 hour compared with SSS and SMP (intranasal) and showed rapid nose-to-brain transport of ST from microemulsion. SME and SMME show 2-fold higher C max and 8-fold higher AUC compared with SMP.…”
Section: Resultsmentioning
confidence: 99%
“…A substantial proportion of migraine patients not only suffer from gastric stasis but also have severe nausea and vomiting, which results in erratic absorption of ST from the gastrointestinal tract. 5 ST is rapidly but incompletely absorbed following oral administration and undergoes first-pass metabolism, resulting in a low absolute bioavailability of 14% in humans. 6 Moreover, the transport of ST across the blood-brain barrier (BBB) is very poor, although evidence of detection of some drug in cerebrospinal fluid (CSF) following high IV dose has been cited in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nasal administration is given at 10 or 20 mg, whereas subcutaneous formulation requires 6 mg every 24 h. The mean bioavailability is 96 % with subcutaneous administration and decreases to approximately 14 and 25 % with oral and nasal administration [27,28]. The lower bioavailability in the oral and nasal route is due to the incomplete absorption followed with high first-pass metabolism.…”
Section: Sumatriptan Succinatementioning
confidence: 99%